Education and hope in troubled times [ visions of change for our children's world - Shapiro, H. Svi (New York : Routledge, 2009)
Bringing together a group of the best creative educational thinkers to reflect on the purpose and future of public education, this collection of original essays by leading social and educational
1. Introduction: education and hope in troubled times -- 2. Education and schooling in the 21st century: the role of the profession -- 3. Is there a place for education in social transformation? -- 4. What is to
Description based on print version record
Includes bibliographical references and index
Keywords: Critical pedagogy; Educational sociology; Educational -- Social aspects -- United States